Pengaruh Corporate Social Responsibility, Kepemilikan Manajerial, Green Banking, Likuiditas, Rentabilitas, dan Aktivitas Perusahaan Pada Perusahaan Sektor Perbankan yang Terdaftar di BEI - Goh, Thomas Sumarsan; Elidawati; Syawaluddin; Cynthia (Politeknik Ganesha Medan, 2024)
Recently, issues related to sustainable development have become an important discussion in the academic, business, and government. As an intermediary, the banking sector has an important role in supporting the economy in Indonesia, so the company must be able to balance the company's interests with stakeholders' interests in improving financial performance to achieve sustainable development that has been determined until 2030. This research aims to examine and analyze corporate social responsibility, managerial ownership, green banking, liquidity, rentability, and company activities on the financial performance of banking sector companies listed on the IDX. The population in this research is 47 banking companies listed on the IDX for 2018-2022. The research sample was 42 banking companies listed on the IDX over five years. The data analysis model in this research is multiple linear regression analysis. The results show that corporate social responsibility, managerial ownership, and green banking partially have no impact on financial performance, but liquidity, rentability, and company activities partially have a significant effect on financial performance in banking sector companies listed on the IDX. Simultaneously, corporate social responsibility, managerial ownership, green banking, liquidity, rentability, and company activities significantly affect the financial performance of banking sector companies listed on the IDX.